Incidence and prevalence of traumatic and non-traumatic wounds and burns and access to wound care in Sierra Leone; data from a nationwide household survey (PRESSCO) 2020 - Jonathan H. Vas Nunes; Alex J. van Duinen; Daniel Boateng; Amidu J. Tommy; Osman Sankoh; Martin P. Grobusch; Håkon A. Bolkan (Heliyon)
Objectives: This wound section of the PREvalence Study on Surgical COnditions (PRESSCO) determines the incidence and prevalence of wounds and burns in Sierra Leone. It further describes access to wound care and wound-related healthcare-seeking behaviour. Methods: Between October 2019 and March 2020, a nationwide cross-sectional household survey was performed. The survey was based on Surgeons OverSeas Assessment of Surgical Need (SOSAS). Additional questions relating to wounds and burns were added. Following randomization, 25 households in 75 clusters were sampled. Severe wounds were clinically examined. Results: Of the 3600 individuals included, 143 had developed 151 wounds, including burns (15.2 %) during the year preceding the interview (incidence 4.2 %). A total of 77 people had 83 wounds and burns at the time of the survey (prevalence 2.3 %), of which 23 were severe (prevalence 0.6 %). Burn incidence and prevalence were 0.6 % and 0.1 %, respectively. Most wounds were on extremities (73.5 %), often resulting from cuts (32.8 %), falls (22.4 %), or road traffic accidents (RTA; 16.4 %). Risk factors for developing a wound were male sex (p = 0.004), older age (p = 0.037) and smoking (p = 0.001). Severe wounds had a median duration of 18 months. For 70.2 % of wounds, care at a health facility was sought. Only 49.9 % of households reported financial capacity to visit a secondary health facility. For 56 (37.1 %) of wounds, the desired care was not obtainable. An estimated 44,000 (95 % CI 29,760–67,410) people in Sierra Leone suffer from a severe wound. An estimated 11,000 (95 % CI 6,416–18,268) annual deaths occur due to wounds, predominantly due to RTA's (66.7 %) and accidental injuries (20.0 %). Conclusions: Wounds and burns account for an extensive burden on the health and economics of the individual, the household, and the Sierra Leonean society. For over one-third of wounds, the desired surgical care was not obtainable.